2023
DOI: 10.1016/j.vaccine.2021.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the spread of serotype-2 vaccine derived-poliovirus outbreak in Pakistan and Afghanistan to inform outbreak control strategies in the context of the COVID-19 pandemic

Abstract: Background Since July 2019, Pakistan and Afghanistan have been facing an outbreak of serotype-2 circulating vaccine derived poliovirus (cVDPV2) in addition to continued transmission of serotype-1 wild poliovirus (WPV1) and SARS-CoV-2 in 2020. Understanding the risks of cVDPV2 transmission due to pause of global vaccination efforts and the impact of potential vaccination response strategies in the current context of COVID-19 mitigation measures is critical. Methods We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Over the past 30 years, wild poliovirus cases have significantly waned by 99%. The reported polio cases at the inception of GPEI in 1988 were 350,000 across 125 countries [ 4 ]. These cases were reduced to 33 reported cases (of polio) in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 30 years, wild poliovirus cases have significantly waned by 99%. The reported polio cases at the inception of GPEI in 1988 were 350,000 across 125 countries [ 4 ]. These cases were reduced to 33 reported cases (of polio) in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…This section begins with a brief overview of each of the 102 studies identified by the search process summarized in Figure 1 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ,…”
Section: Resultsmentioning
confidence: 99%
“…The studies identified for IC for 2020–2024.25 showed its continued focus on statistical analyses of existing surveillance data and data collected as part of prospective trials or challenge studies and included a new focus area related to the development of a poliovirus direct detection method. With respect to transmission modeling, IC applied an SC model to characterize the spread of serotype-2 vaccine-derived-poliovirus outbreaks in Pakistan and Afghanistan to inform outbreak control strategies in the context of the COVID-19 pandemic [ 47 ], which built on a statistical analysis that quantified movement patterns and vaccination status in high-risk mobile populations [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…For one, we model observed cases rather than asymptomatic infections, which are necessarily more widespread than observed cases. One could account for this by examining risk in a longer window over which latent infections would be expected to result in an observed case, or by constructing a model that estimates latent infections [16]. However, models with latent infections are computationally intensive and typically make stronger assumptions on disease dynamics [17].…”
Section: Model Limitations and Future Workmentioning
confidence: 99%